Blynk-enabled notification workflow for ESP8266 security alerts in resource-constrained deployments - Dahalan, Abdul Halim; Hassim, Nurulhalim (Research and Scientific Innovation Society, 2026)
The increasing vulnerability of physical asset containers such as fund and donation boxes has highlighted the need for affordable and responsive security solutions. This paper presents a Blynk-enabled notification workflow integrated with an ESP8266-based alert system designed for deployment in resource-constrained environments. The proposed system combines ultrasonic and force sensors with an ESP8266 Wi-Fi module to detect unauthorized access, tampering, or movement. Upon trigger activation, the system generates a local audible alarm and transmits real-time notifications to stakeholders through the Blynk mobile application. The workflow emphasizes lightweight communication, minimal power consumption, and reliable message delivery over standard Wi-Fi networks. Experimental evaluation demonstrates effective threshold-based detection for force and distance sensing, along with acceptable battery consumption for continuous monitoring scenarios. Results indicate that the integration of Blynk simplifies remote monitoring while maintaining responsiveness under limited hardware and energy constraints. The findings confirm that low-cost IoT platforms can deliver practical security alerting solutions suitable for small-scale asset protection and similar applications.